2015
DOI: 10.1007/s00425-015-2246-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of mRNA-like noncoding RNAs in Salvia miltiorrhiza

Abstract: Identification and characterization of 5,446 mlncRNAs from Salvia miltiorrhiza showed that the majority of identified mlncRNAs were stress responsive, providing a framework for elucidating mlncRNA functions in S. miltiorrhiza. mRNA-like noncoding RNAs (mlncRNAs) are transcribed by RNA polymerase II and are polyadenylated, capped and spliced. They play important roles in plant development and defense responses. However, there is no information available for mlncRNAs in Salvia miltiorrhiza Bunge, the first Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…BLAST analysis of the Arabidopsis , rice and S. miltiorrhiza sequences against the S. miltiorrhiza transcriptomic unigenes assembled from ESTs and RNA-seq reads [ 42 ] showed that unigenes could be identified for nine of the 22 cloned S. miltiorrhiza GA metabolism pathway genes. It includes SmKO , SmKAO1 , SmGA3ox2 , SmGA20ox2 – SmGA20ox4 , SmGA2ox3 , SmGA2ox5 and SmGA2ox11 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…BLAST analysis of the Arabidopsis , rice and S. miltiorrhiza sequences against the S. miltiorrhiza transcriptomic unigenes assembled from ESTs and RNA-seq reads [ 42 ] showed that unigenes could be identified for nine of the 22 cloned S. miltiorrhiza GA metabolism pathway genes. It includes SmKO , SmKAO1 , SmGA3ox2 , SmGA20ox2 – SmGA20ox4 , SmGA2ox3 , SmGA2ox5 and SmGA2ox11 .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, two differently spliced AtKO ( GA3 ) mRNAs had been cloned, sequenced and detected using Northern hybridization [ 45 ]. In order to examine whether genes associated with GA metabolism underwent AS events, we analyzed the assembled S. miltiorrhiza transcriptome [ 42 ] for the 22 cloned GA metabolism pathway genes. Sequence comparison among unigenes, the cloned cDNAs and the genomic DNA showed that SmKO , SmGA20ox3 , SmGA2ox3 and SmGA2ox11 produced splice variants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-coding RNAs, including small RNAs and long non-coding RNAs, play significant regulatory roles in many aspects of plants (Lu et al, 2005, 2007, 2008; Lu S. et al, 2013; Li D. et al, 2015; Wang et al, 2015). Various microRNAs have been identified to be associated with secondary metabolism (Wu et al, 2012; Lu S. et al, 2013; Fan et al, 2015; Wei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%